Efeito da radiação micro-ondas sobre processos oxidativos em óleo e gordura submetidos à fritura de batata inglesa - Mascarin, Laura Gizele (2014)
The aim of this work was to employ the microwave radiation in the processes of frying potatoes (Solanum tuberosum L.), and evaluate of the impact on lipids oxidation parameters and mass transfer in the product. The potatoes (Asterix CV.) were cut in stick form and subjected to conventional system of fry (CF) and adapted microwave system (MW) in soybean oil (SO) and vegetable fat (VF), under the same conditions of mass, volume, time and temperature of process. Physico-chemical quality parameters of the potatoes and SO/VF were determined. The results of the moisture content indicated that dehydration in potatoes was 45% higher in microwave system, and in addition a greater absorption of lipids was observed. The contents of total polar compounds in SO were greater than 25% in MW and CF after 5 and 7 days of frying, respectively, while the VF systems did not exceed 19.5% at 20 days of use. The peroxide values presented higher values for SO in MW system. High values of conjugated dienes parameters, peroxide values, total polar compounds and refractive index in treatments with MW. Possibly the major loss of water from the product in these system has favored the hydrolytic and oxidative reactions. Regarding the SO fatty acids a decreased was observed of monounsaturated 4.0 and 2.0%, and poly-unsaturated 6.3 and 3.6%, respectively for MW and CF, and VF presented an opposite behavior in both systems. The MW frying process provided a higher inside temperature of the potatoes in both fats, SO and VF. When OS was only heated with MW radiation observed, based on the results, a similar behavior to the conventional system in almost all parameters. The application of MW for frying potato in chips form showed favorable values of mass transfer and heat, obtaining a product with similar characteristics to the reference product. Thus it was demonstrated a potential use of MW radiation in the frying potato process and its use only as a heating source for the OS and VF.